AN ANALYSIS OF THE OPSONIC AND TROPIC ACTION OF NORMAL AND IMMUNE SERA BASED ON EXPERIMENTS WITH THE PNEUMOCOCCUS - Ward, Hugh K. (The Rockefeller University Press, 1933)
1. In normal unheated human serum, virulent pneumococci may be prepared for phagocytosis by two separate antibodies, acting in conjunction with complement. One of these is the type-specific anticarbohydrate antibody reacting with the carbohydrate fraction of the pneumococcus. The other is probably also a type-specific antibody, but quite distinct from the former, and therefore must react with a different antigenic constituent of the bacterium. 2. In the normal human serum heated to 56°C., these two antibodies may, after prolonged contact with the organism, promote phagocytosis of the pneumococcus without the adjuvant action of complement. 3. Although these two antibodies are equally effective in the phagocytosis of 24 hour culture organisms by normal blood, the anticarbohydrate antibody tends to become the predominant factor as the pneumococci approach the state in which they exist in the animal body. 4. In so far as we have been able to show, the anticarbohydrate antibody is the only antibody in immune serum which can induce phagocytosis. This substance by itself is active in a phagocytic system, but just as in the normal serum, complement enhances its effect. The failure to demonstrate the presence in the immune serum of an antibody, distinct from the anticarbohydrate antibody, analogous to that found in the normal serum, may be due to the experimental difficulty of removing all the anticarbohydrate antibody from a concentrated immune serum. 5. Thus it is seen that a single well defined antibody (the anticarbohydrate antibody) may be responsible for the phagocytic action of normal unheated serum, normal heated serum, inactivated immune serum, and immune serum activated by complement. These facts appear to us to invalidate Neufeld's division of the phagocytic antibodies into (a) bacteriotropins (antibodies, the phagocytic titre of which is not raised by the addition of complement); (b) opsonic antibodies (antibodies, comparable to the lysins, which are only active in the presence of complement). 6. Complement alone is incapable of inducing phagocytosis of the pneumococcus. In the phagocytic process, it appears simply to increase the speed at which the reaction takes place. Its role may be compared to that of a catalyst in a chemical reaction. 7. On the basis of these findings, it is proposed that the term "tropin" be discarded as misleading and unnecessary, and that the term "opsonin" be retained to denote any heat-stable antibody which prepares bacteria for phagocytosis. Contrary to current usage, it would not suggest a combination of antibody with complement.